Amorphous Carbon Interconnected Ultrafine CoMnP with Enhanced Co Electron Delocalization Yields Pt‐Like Activity for Alkaline Water Electrolysis. (26th February 2022) - Xu, Yanchao; Wei, Shuting; Gan, Linfeng; Zhang, Lei; Wang, Feng; Wu, Qiong; Cui, Xiaoqiang; Zheng, Weitao
Abstract: Constructing earth‐abundant water splitting electrocatalysts performing platinum‐like activity is promising for the hydrogen economy but still a challenging task. Herein, the ultrafine CoMnP nanocrystals confined in amorphous carbon nanosheets are designed and implemented by a topological transformation strategy from layer double hydroxide/carbon interconnected structures in one single nanosheet. The unique interconnected structure favors the exposure of active sites and enables stronger electronic coupling effect between the two phases. Experimental results and density functional theory simulations reveal that the surrounding amorphous carbon and Mn dopants synergistically enable better electron delocalization capacity of Co sites, potentially providing enhanced conductivity and optimal reaction energetics during hydrogen evolution. The as‐prepared catalyst exhibits hydrogen evolution reaction performances superior to that of Pt/C under alkaline media with an overpotential of 114 mV at 100 mA cm –2 . This work highlights the rational fabrication of transition metal‐based electrocatalysts via spatially confined growth for efficient water electrolysis. Abstract : A unique interconnected structure with ultrafine CoMnP nanocrystals embed into carbon nanosheets is prepared via a spatially confined synthetic method. Surrounding amorphous carbon and Mn dopants synergistically enable better electron delocalization capacity of Co sites, endowing the CoMnP/carbon interconnected structures with enhanced conductivity and optimal reaction energetics during hydrogen evolution under alkaline media.